The Effect of Environment Performance, Capital Structure, and Company Size on Financial Performance - Alfitri, Destiana Nur; Nugroho, Wawan Sadtyo; Nurcahyono, Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
One way to assess a company's success is to look at its financial results. Due to the COVID-19 pandemic, the financial performance of the industrial sector plummeted. When a company's financial performance plummets, there is no choice but to declare bankruptcy. Based on data collected from the Indonesia Stock Exchange (IDX) manufacturing business between 2018 and 2021, this study will analyze the relationship between environmental performance, capital structure, company size and financial success. This study uses quantitative methods based on cross-sections of 25 financial statements covering 2018–2021. A combination of descriptive statistics and multiple regression was used in this study. The statistical program SPSS 24 was used for this study. According to research, a company's size, capital structure, and environmental performance all play a role in its financial success. Discussing financial performance is a common theme in many studies. For the latest version of the study, researchers included variables such as capital structure, company size, and period